1985
DOI: 10.1051/rnd:19850701
|View full text |Cite
|
Sign up to set email alerts
|

The influence of an essential fatty acid deficient-diet on the reproductive performance of female rats

Abstract: Summary. Several Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…A high post-natal mortality was observed in the pups born to dams fed on an EFA-deficient diet in the present experiments. Similar rates of pup mortality were reported in litters born to first- (Parlanti & Orellana, 1985) and secondgeneration EFA-deficient rats (Sinclair & Crawford, 1973 ;Alling et al 1974). In our study, triene: tetraene for liver phospholipids in expired pups had a mean value of 0.7, a value not exceptionally high when compared with those observed in deficient animals in the postweaning experiments.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A high post-natal mortality was observed in the pups born to dams fed on an EFA-deficient diet in the present experiments. Similar rates of pup mortality were reported in litters born to first- (Parlanti & Orellana, 1985) and secondgeneration EFA-deficient rats (Sinclair & Crawford, 1973 ;Alling et al 1974). In our study, triene: tetraene for liver phospholipids in expired pups had a mean value of 0.7, a value not exceptionally high when compared with those observed in deficient animals in the postweaning experiments.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to the direct, or indirect, effects on protein and energy balance, several animal experiments have demonstrated that maternal EFA deficiency during pregnancy and lactation resulted in growth retardation in the foetuses (Menon et al 1981) and offspring (Alling et al 1974;Menon et al 1981;Parlanti & Orellana, 1985). Arachidonic acid in particular has been shown to have growth-promoting effects mediated through its role in the synthesis of prostaglandins and other eicosanoids (Koletzko & Braun, 1991).…”
mentioning
confidence: 99%
“…It is well established that essential-fatty-acid deficiency in the rat leads to degeneration of the testis, with concomitant infertility, in males (Ahluwalia et al 1967;Marzouki & Coniglio, 1982). In females, though they may conceive, fetuses are often reabsorbed, animals abort or young ones are stillborn (Mohrhauer & Holman, 1967;Menon et al 198 I ) ; the frequency of irregular oestrous cycles, with an increased incidence of prolonged dioestrus, prolonged period of gestation, reduced litter size, and increased pup mortality, are usually significantly higher (Satomi & Matsuda, 1973;Parlanti & Orellana, 1985). It seems possible that high concentrations of trans-fatty acid isomers, as found in hydrogenated dietary oils, could also adversely affect the reproduction of laboratory rats, though that effect would be more probable at lower levels of essential fatty acids (Holman & Aaes-Jorgensen, 1956;Alfin-Slater et al 1957;Emken, 1984).…”
mentioning
confidence: 99%
“…In fact, the reviewed data and information by various researchers showed an improvement of seminal characteristics in males as well an enhancement of the fertility and prolificacy in female animals when fed on ration contained vegetable oils, in one the hand as have been found in rabbits (Christ et al, 1996), horses (Squires, 2006), rats (Naseem et al, 2007), boars (Estienne et al, 2008), dogs (Rocha et al, 2009), turkeys (Zaniboni andCerolini, 2009), quails (Al-Daraji et al, 2010), and ducks (Ghonim et al, 2010). On the other hand, it is well established that essential-fatty-acid deficiency leads to degeneration of the testis with concomitant infertility (Ahluwalia et al, 1967;Marzouki and Coniglio, 1982;Wathes et al, 2007), and leads to prolonged diestrus, abortion, or giving birth to stillborn fetuses (Menon et al, 1981;Parlanti and Orellana, 1985). Meanwhile, Pascual et al (1999) did not encounter any differences in the prolificacy of does rabbits supplemented with soybean oil ration (at 99 to 117 g per kg DM) compared to control diet (at 26 g per kg DM), as well Kelso et al (1997) who observed no differences in sperm motility during a 49-week experiment when fed a rich ω 3 or ω 6 diets to turkeys, while Yaakub et al (2009) found out that spermatogenesis was altered in rams fed on palm kernel cake-based ration.…”
Section: Introductionmentioning
confidence: 99%